SYNTHESIS AND CHARACTERIZATION OF COPPER-BASED ZEOLITIC IMIDAZOLATE FRAMEWORKS PHOTOCATALYST FOR CO2 REDUCTION TO METHANOL UNDER VISIBLE LIGHT IRRADIATION. - GOYAL, SONAM (2019)
Photocatalytic CO2 reduction to methanol is considered as one of the feasible ways to utilize excess CO2 and mitigates global warming issue